Implementasi Pendidikan Berbasis Sistematika Wahyu - Maryam, Siti; Riyadi, Ahmad; Saugi, Wildan (el Buhuth: Borneo Journal of Islamic Studies, 2019)
This research aims to find out the implementation of revelation systematic based education on the characters of third grade students of SD Integral Rahmatullah Lempake, North Samarinda. The approach used in this research was qualitative. The type of the research was descriptive. This research was conducted at SD Integral Rahmatullah Lempake, North Samarinda. The data collection techniques were observation, interviews and documentation. The data analysis technique used resource clarification, data reduction, data presentation, conclusion and verification.The implementation of revelation systematic based education on the characters of third grade students of SD Integral Rahmatullah Lempake, North Samarinda are carried out through the approaches of: first, teacher modeling, second habituation at school such as Dhuha prayer, infaq (charity), etc. The supporting and obstructing factors in the implementation of revelation systematic based education on the characters of third grade students of SD Integral Rahmatullah are 1) supporting factors: first, the role of the school foundation on the policy of the programs implemented by the school, second, the role of the teachers in implementing the revelation systematic in learning, third, the active role of parents in the school program; 2) obstructing factors: first, the teachers’ character which is sometimes inconsistent in modeling, while teachers from outside are less knowledge on the revelation systematic, second, parents’ unconcern on the students’ bad behavior at home.